Gestão da satisfação e da fidelidade de consumidores :um estudo dos fatores que afetam a satisfação e a fidelidade no mercado de turismo - Rodrigues, Joab Maciel Saldanha (2003)
The corporative strategies have been systematically changing since the middle of the 90´s by including measurement of satisfaction and loyalty of the consumers in their organization. strategies. This essay presents a study on the factors that influence on the satisfaction and loyalty of the consumers, and is based on national models of satisfaction rates. For this essay, the new Norwegian model was used. During the period of 01/06/03 until 02/14/03, a field research was developed and applied to 230 tourists visiting the city of Natal/RN